Green Tea Polyphenol-Sensitive Calcium Signaling in Immune T Cell Function - Singh, Yogesh; Salker, Madhuri S.; Lang, Florian (Frontiers in Nutrition, 2021)
Polyphenol compounds found in green tea have a great therapeutic potential to influence multiple human diseases including malignancy and inflammation. In this mini review, we describe effects of green tea and the most important component EGCG in malignancy and inflammation. We focus on cellular mechanisms involved in the modification of T cell function by green tea polyphenol EGCG. The case is made that EGCG downregulates calcium channel activity by influencing miRNAs regulating expression of the channel at the post-transcriptional level.